Size distribution and growth parameters of blue swimming crab (Portunus pelagicus, Linnaeus 1758) in Awur Bay, Jepara - Azzahra, Rizqina Nafa Nur; Saputra, Suradi Wijaya; Rudiyanti, Siti (Acta Aquatica: Aquatic Sciences Journal, 2024)
Blue swimming crab (Portunus pelagicus) is a fishery commodity that has important economic value. One of the catch landings in Teluk Awur, Jepara is blue swimming crab. Intensive crab catching carried out with small sizes has an effect on decreasing crab stocks in the waters. This study aims to determine the size distribution, the relationship between carapace width and weight, growth parameters and recruitment patterns. The research was conducted in May, June, July and August 2022 in the waters of Teluk Awur, Jepara. Sampling using systematic sampling method. The data collected is carapace width (mm) and crab weight (grams). Data analysis was performed using FiSAT II software. The results of the analysis of the relationship between carapace width and weight showed that the growth of the male crab was positive allometric and the growth of the female crab was isometric, with the equation of the male crab W = 0.0000214cW3.251 and the female crab W = 0.0000232cW3.220. The growth parameters obtained by the equation of the male and female crabs were cWt = 158,55(1- e(-1,2(t+0,083))], and cWt = 158.55(1 - e(-0.67(t+0.152) ))). The peak of male crab recruitment was in October at 22,71%, while the female crab was in May at 13,52%, indicating that in that month new crab individuals were added. Based on these results, the stock of crab resources in Jepara's Awur Bay must always be considered and always support the recruitment process of crab. Beside that, the goverment can enforce management of crab fishing.Keywords: Allometric; Carapace Width; Crab; Recruitment